Solvation free energies of nucleic acid bases in ionic liquids - Jumbri, K. (Taylor and Francis Ltd., 2017)
The solvation free energies of five nucleic acid bases in CnbimBr (where n = 2, 4, 6) ionic liquids (ILs) were computed using the Bennett acceptance ratio (BAR) method employing molecular dynamics simulations. The computed free energies using BAR were in agreement with other methods. The large and negative predicted free energies of the bases in ILs indicated that the bases were better solvated in the ILs rather than in water. Hydrogen bonding interactions between polar sites of the bases and ILs’ ions significantly contributed to the solvation mechanism. © 2016 Informa UK Limited, trading as Taylor & Francis Group.